Appendiceal adenocarcinoma with breast metastases. Issue 5 (14th May 2021) - Davies, Timothy; Chouari, Tarak; Ray, Christopher; Elgammal, Suzanne
Abstract : Malignant lesions of the vermiform appendix make up a rare subset of colorectal cancer. While colorectal cancer frequently metastasises to the liver, lung, regional lymph nodes and peritoneum, metastasis to the breast is extremely rare. Here, we describe the case of an 84-year-old woman who had the incidental finding of appendiceal adenocarcinoma following emergency laparoscopic appendectomy. She declined further operative or adjuvant treatment for her disease. She represented 1 year later with metastatic appendiceal adenocarcinoma disease to her left breast. A simple mastectomy for symptomatic treatment was performed. In this report, we describe the first case of appendiceal adenocarcinoma metastases to the breast. Due to its rarity, there is a paucity of evidence related to the management of this condition. The limited evidence is reviewed and discussed.